Self-esteem in Greek Dialysis Patients: the Contribution of Health Locus of Control (Iranian Journal of Kidney Diseases, 2012)
Introduction. Chronic kidney disease is a permanent condition which requires renal replacement therapy (hemodialysis, peritoneal dialysis, or transplantation) to maintain life. The present study aimed to investigate the association of self-esteem with health locus of control in dialysis patients. Materials and Methods. A sample of 144 patients was recruited from 3 General Hospitals in the broader area of Athens, consisting of 84 patients undergoing in-center hemodialysis and 60 patients on continuous ambulatory peritoneal dialysis. Measurements were conducted with the World Health Organization Quality of Life instrument, in which self-esteem is addressed by 1 item, and the Multidimensional Health Locus of Control inventory. Results. The results indicated that self-esteem had a significant positive association with internal health locus of control.  Self-esteem was also inversely related to the dimension of important others measured by the Multidimensional Health Locus of Control inventory. Conclusions. Findings of this study provide evidence that there is a strong relation between self-esteem and health locus of control in dialysis patients.